2013
DOI: 10.1136/bmjopen-2012-002348
|View full text |Cite
|
Sign up to set email alerts
|

Real-world outcomes of US employees with type 2 diabetes mellitus treated with insulin glargine or neutral protamine Hagedorn insulin: a comparative retrospective database study

Abstract: ObjectivesTo compare real-world outcomes of initiating insulin glargine (GLA) versus neutral protamine Hagedorn (NPH) insulin among employees with type 2 diabetes mellitus (T2DM) who had both employer-sponsored health insurance and short-tem-disability coverages.DesignRetrospective cohort study.SettingMarketScan Commercial Claims and Encounters/Health and Productivity Management Databases 2003–2009.ParticipantsAdult employees with T2DM who were previously treated with oral antidiabetic drugs and/or glucagon-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 49 publications
2
58
0
2
Order By: Relevance
“…For example, in a study of a large commercially insured insulin-na€ ıve population in the US, Ascher-Svanum et al found that only 18% of the people with T2DM who initiated insulin continued treatment in the year after initiation without any interruption or discontinuation 10 . With regards to basal insulin in particular, studies have found that approximately 55-80% of people with T2DM (identified from large commercial insurance databases) who were prescribed insulin glargine remained treatment persistent within the year after initiation [11][12][13][14] . In a separate study evaluating persistence with injectable antihyperglycemic medications among a managed care population, Cooke et al reported that 29% of patients initiating basal insulin or exenatide were persistent at 12 months after initiation 15 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study of a large commercially insured insulin-na€ ıve population in the US, Ascher-Svanum et al found that only 18% of the people with T2DM who initiated insulin continued treatment in the year after initiation without any interruption or discontinuation 10 . With regards to basal insulin in particular, studies have found that approximately 55-80% of people with T2DM (identified from large commercial insurance databases) who were prescribed insulin glargine remained treatment persistent within the year after initiation [11][12][13][14] . In a separate study evaluating persistence with injectable antihyperglycemic medications among a managed care population, Cooke et al reported that 29% of patients initiating basal insulin or exenatide were persistent at 12 months after initiation 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Несмотря на то что человеческий НПХ-инсулин по-прежнему остается эффективным и востребованным базальным инсулином, аналоги длительного действия, первым из которых стал гларгин, быстро заняли свою нишу в лечении диабета как препараты с меньшей крат-ностью введения и более низким риском развития гипо-гликемии [19,20].…”
Section: рисунок рекомендации по выбору режима инсулино-терапииunclassified
“…Важным результатом яви-лось то, что нормализация уровня ГПН при терапии глар-гином никак не отразилась на исходах ССЗ у участников с ранними стадиями дисгликемии в течение всего периода Одной из простых, но достаточно эффективных схем для старта является применение готовых смесей инсулина в режиме от одной до трех инъекций в сутки исследования и не сопровождалась увеличением общей смертности. Кроме того, было показано, что применение гларгина позволило замедлить прогрессирование заболе-вания от стадии предиабета к явному СД2 на 28% [20].…”
Section: рисунок рекомендации по выбору режима инсулино-терапииunclassified
“…3 In another US study, the total overall health care costs were similar for insulin glargine and NPH insulin patients, as were the total diabetes-related health care costs. 4 In German studies, lower treatment costs were found under insulin glargine compared to insulin detemir 7 and human insulin 8 based on longer persistence. A database study from the US indicated that early discontinuation of insulin (basal or premixed insulin) in type 2 diabetes was related to approximately 10% higher acute health care costs compared to patients who did continue their insulin therapy.…”
mentioning
confidence: 99%
“…2 Few studies have examined the persistence of type 2 diabetes patients on BOT in a real -world setting. [3][4][5][6][7] There is evidence from German studies that BOT initiation with insulin glargine may be associated with a higher persistence compared to initiation with NPH insulin. [5][6] Little information is available about the impact of basal insulin changes on associated health care costs in real-world primary care settings.…”
mentioning
confidence: 99%